High-throughput sequencing reveals an altered T cell repertoire in X-linked agammaglobulinemia - Ramesh, Manish (Clin Immunol, 2015)
To examine the T cell receptor structure in the absence of B cells, the TCR β CDR3 was sequenced from DNA of 15 X-linked agammaglobulinemia (XLA) subjects and 18 male controls, using the Illumina HiSeq platform and the ImmunoSEQ analyzer. V gene usage and the V–J combinations, derived from both productive and nonproductive sequences, were significantly different between XLA samples and controls. Although the CDR3 length was similar for XLA and control samples, the CDR3 region of the XLA T cell receptor contained significantly fewer deletions and insertions in V, D, and J gene segments, differences intrinsic to the V(D)J recombination process and not due to peripheral T cell selection. XLA CDR3s demonstrated fewer charged amino acid residues, more sharing of CDR3 sequences, and almost completely lacked a population of highly modified Vβ gene segments found in control DNA, suggesting both a skewed and contracted T cell repertoire in XLA.